2018
DOI: 10.1590/1807-3107bor-2018.vol32.0077
|View full text |Cite
|
Sign up to set email alerts
|

Systemic diseases and other painful conditions in patients with temporomandibular disorders and migraine

Abstract: This was a cross-sectional study conducted in a sample of 352 individuals. Participants were stratified into three groups according to the presence of painful TMD and M: controls [individuals free of TMD and any headache (HA)]; TMD only (presence of painful TMD, but free of any HA); and TMD+M (presence of painful TMD and M). TMD was classified according to the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) - Axis I. Nonspecific physical symptoms (NSPS) were assessed by RDC/TMD - Axis II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Since vitamin D deficiency is more prevalent in women, and is usually associated with poorer musculoskeletal health in community-living people in Taiwan [ 39 ], it is not surprising that female sex might be a risk factor for TMD. In a previous study by Contreras [ 35 ], peptic ulcer disease has been associated with the presence of painful TMD in the univariate analysis, whereas this association was not shown in the multivariable model. In our current study, we found peptic ulcer disease to be an independent risk factor for incident TMD in SA patients.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Since vitamin D deficiency is more prevalent in women, and is usually associated with poorer musculoskeletal health in community-living people in Taiwan [ 39 ], it is not surprising that female sex might be a risk factor for TMD. In a previous study by Contreras [ 35 ], peptic ulcer disease has been associated with the presence of painful TMD in the univariate analysis, whereas this association was not shown in the multivariable model. In our current study, we found peptic ulcer disease to be an independent risk factor for incident TMD in SA patients.…”
Section: Discussionmentioning
confidence: 87%
“…Traditionally, female sex has been suggested as a risk factor for the development of TMD. For example, Contreras et al found a higher TMD prevalence in women [ 35 ]. Sexual hormones, especially estrogen, might play an important role in the sensitivity of pain, even in the muscles of mastication, and therefore, might contribute to the pathogenesis of TMD [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…TMD most often coexist with other systemic diseases which can modulate the course of TMD. There are more severe symptoms observed in patients with comorbidities than with isolated TMD [ 65 , 66 ]. Abnormalities in female reproductive hormone levels correlate with the frequency of TMD, intensify their symptoms, extend their duration or hinder the effectiveness of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous factors can cause condylar angle discrepancies, [9,10] so it is important to distinguish the normal and abnormal condylar anatomy in order to recognize its diseases and disorders. In our study, we excluded any patients with disease that could alter the normal anatomy; such as systemic diseases, [11] bone diseases, [12] trauma [13] and any metabolic diseases. [14] In a study done by Pamukcu et al, [9] temporomandibular joints of 3 groups of people were investigated on healthy controls and patients unilateral and bilateral temporomandibular joint disease.…”
Section: Discussionmentioning
confidence: 99%